Seismic Retrofit of Elevated Steel Water Tanks - Sambu Potty, Narayanan (2008)
The Indian Standard “Criteria for Earthquake Resistant Design of Structures: IS 1893-1984” was revised in 2002. Areas in earthquake zone 1 were merged to earthquake zone 2 and the place Killari is now in earthquake zone 3. The seismic zone factors have also changed. Response spectra are specified for 3 types of founding soil strata and a response reduction factor was been introduced. Elevated water tanks are vulnerable to earthquake, owing to large mass concentrated at the top of a relatively slender supporting structure. In this paper, existing elevated steel water tanks in India designed using IS 1893-1984 was checked for safety as per revised code (IS 1893-2002) by carrying out static and forced dynamic analysis. It was observed that the structure was unsafe due to under-estimation of seismic load as per old code provisions. Retrofit measures such as additional structural elements and passive devices like viscous and friction dampers were modelled and structure analysed again to check for compliance with the revised code. Conclusions drawn from this study are presented.